(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the knowledge, attitudes, practices, and related factors regarding safe injection among nurses at Ho Chi Minh city Hospital of Dermato-Venereology from July to September 2024. Methods: A descriptive cross-sectional study was conducted, involving all nurses performing injections in the injection rooms and clinical departments. Data were collected using a structured questionnaire to assess knowledge and attitudes, as well as a checklist for direct observation of practices. Results: A total of 85 nurses participated in the study. Of these, 94.1% demonstrated adequate general knowledge of safe injection; 82.4% had appropriate attitudes; and 81.2% met standard practices, with 81.3% performing intramuscular injections and 81.0% performing subcutaneous injections correctly. Conclusion: Regular training, close monitoring of injection practices, and continuous awareness enhancement are needed to improve the quality of safe injection in hospitals.